The effect of secure attachment on family relationships and peer bullying in adolescents: the mediating role of positive childhood experiences - Çiçek, İlhan and Korkmaz, Zafer and Ünsal, Fırat and Shalal Alanazi, Zainab and Gómez-Salgado, Juan and Yıldırım, Murat (Frontiers in Psychology, 2025)
AimsThis study examines whether positive childhood experiences (PCEs) mediate the relationship between secure attachment and family conflict, peer bullying, and family cohesion in adolescents.MethodThe sample includes 574 high school students [301 female (52.4%), 273 male], aged 14 to 18 years (M = 16.28, SD = 1.45). Participants completed the Brief Family Relationships Scale, the Attachment Styles Scale, the Peer Bullying Scale, and the Positive Childhood Experiences Scale.ResultsFindings revealed that secure attachment was positively associated with PCEs, which in turn were linked to greater family cohesion and lower levels of family conflict and peer bullying. Mediation analyses confirmed that PCEs significantly mediated the relationship between secure attachment and family conflict, peer bullying, and family cohesion.ConclusionThese findings suggest PCEs as a key variable linking secure attachment to adolescents’ social and family adjustment. They emphasize the critical role of nurturing supportive developmental environments across diverse contexts.